Zooplankton diversity of a protected and vulnerable wetland system in southern South America (Llancanelo area, Argentina) - D'ambrosio, Débora Sabina (2016)
In arid regions, climatic conditions exert a great control on the aquatic systems present, but recent changes in climate have produced an enhanced salinization of the aquatic environments located there. Consequently, a major reduction in biodiversity would be expected in those wetlands that were originally fresh water. Salinity is a principal cause of reduced biodiversity particularly in zooplankton because few of those species can adapt to the salt pressure of saline environments. Therefore, the aim of this study was to gain essential information on the diversity of aquatic invertebrates in Llancanelo basin by focussing the analysis on the zooplankton community and exploring seasonal and spatial differences in the zooplankton assemblages of this vulnerable wetland system within an arid region of Argentina. Seasonal samples were taken at 9 sites in the basin (a shallow lake, 4 springs, streams, and the Malargüe River). A total of 45 species were identified. The zooplankton abundance in the lake displayed a clear seasonal contrast and was higher than that recorded in the springs and lotic environments. Boeckella poopoensis, Fabrea salina, and Brachionus plicatilis predominated in the lake, indicating their halophilia. The presence of the crustaceans Alona sp., Macrocyclops albidus, and Paracyclops fimbriatus was restricted to the springs; whereas Notholca labis and Notholca squamula were found only in running water. The zooplankton species richness in the Llancanelo area is low because of both the salt content in the lake and the irregularity of freshwater entry in all locations during the annual cycle.